Ekstraksi Polifenol Total dari Daun Kadamba (Mitragyna speciosa Korth) Menggunakan Metode Choline Chloride-Sorbitol based Microwave Assisted Extraction - Ramila Hidayati; Dewi Rahmawati; Islamudin Ahmad (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
This research was conducted to determine the influence of the use of the choline chloride-sorbitol based microwave assisted extraction (MAE) method against the total extraction of polyphenols from the leaf Kadamba (Mitragyna speciosa Korth). Simplisia extracted using solvent (green solvent) choline chloride-sorbitol with a ratio of 1:1; 1:2 and 1:3 g/g with sample and solvent ratio of 1:10 g/mL, microwave strength is 50% watt and performed for 10 minutes, the extract solution has been obtained and then done determination of total levels of polyphenols by using folin ciocalteu reagents and further measured its absorption with the UV-VIS spectrophotometer device at a wavelength of 770 nm. Based on the results of the study, obtained the levels of polyphenols from each comparison of solvent used against the sample of 334 mg of GAE/g samples (1:1 g/g solvent); 372 mg GAE/g samples (1:2 g/g solvents) and 299 mg of GAE/g samples (1:3 g/g solvents). Based on the results of the study can be concluded that the method of choline chloride-sorbitol based microwave assisted extraction (MAE) can be used to extract the polyphenols from Kadamba leaves easily, quickly and efficiently.